THE LEADERSHIP OF TEACHERS AND THE USE OF PSYCHO-PEDAGOGICAL PUNISHMENT IN THE REPUBLIC OF KOSOVO IN THE REGION OF PRIZREN - Batjar Halili (European Scientific Journal, ESJ, 2014)
Punishment has great educative virtues. Due to this point of view, the teachers use it often, sometimes even with extreme forms. Many studies have pointed that the discipline in class can be placed better through the motivation of the self-control of the pupils rather than through the external control (http://www.filebox.vt.edu/users/dstrater/RewardsPunishmentDebate.pdf).The purpose of this research is to verify the forms of psycho-pedagogic punishments that have been used to the pupils in the 5 communes of the area of Prizren. Regarding their perceptions about the verbal and non-verbal punishments, the students have shown a high demonstration of credibility with the coefficient Cronbach alpha = .639. Most of the questions have been considered seriously and have been answered toward the demonstration of an autocratic leadership system. Hence, the questions that have the higher coefficient of correlations have shown controversial stability in other statistic performances and have also shown the dominance of the verbal punishments over the verbal ones.